Progress in research on and classification of surgical methods of arthroscopic reconstruction of the ACL and ALL using a shared tendon graft through the femoral tunnel - Guo, Ziteng; Liu, Fei (Frontiers in Surgery, 2023)
Anterior cruciate ligament (ACL) tear is a common clinical injury, and ACL reconstruction has reached a very mature stage. However, with the accumulation of cases, scholars have found that isolated ACL reconstruction may not completely solve the problem of knee rotational stability. With the increase in our understanding of knee joint structure, ACL combined with anterolateral ligament (ALL) reconstruction has become accepted by most scholars, and this operation has also achieved good clinical results. At present, there is no unified surgical method for ACL combined with ALL reconstruction. There are differences in bone tunnel location, reconstruction methods, and graft selection. Compared with the independent reconstruction of the ACL and ALL during the operation, shared tendon graft reconstruction of the ACL and ALL has the advantages of preserving tendon and avoiding tunnel convergence. So far, there is no relevant literature summarizing the reconstruction of the ACL and ALL with a shared tendon graft. This paper reviews the anatomic study of the ALL, the study of isometric points, surgical indications, and surgical methods and their classification for shared tendon graft reconstruction of the ACL and ALL.